2021
DOI: 10.1007/s11010-021-04201-6
|View full text |Cite
|
Sign up to set email alerts
|

Turmeric and its bioactive constituents trigger cell signaling mechanisms that protect against diabetes and cardiovascular diseases

Abstract: Turmeric, the rhizome of Curcuma longa plant belonging to the ginger family Zingiberaceae, has a history in Ayurvedic and traditional Chinese medicine for treatment of chronic diseases, including metabolic and cardiovascular diseases (CVD). This parallels a prevalence of age- and lifestyle-related diseases, especially CVD and type 2 diabetes (T2D), and associated mortality which has occurred in recent decades. While the chemical composition of turmeric is complex, curcuminoids and essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 136 publications
(151 reference statements)
0
47
0
2
Order By: Relevance
“…Turmeric, a powder of the rhizomes of Curcuma longa L. (Zingiberaceae), is a well-known spice additive that is ubiquitous in Asian cuisine [ 10 ]. Turmeric is also a staple component of Ayurveda and traditional Chinese medicine and has been used as a remedy for various chronic diseases, such as cardiovascular disease and diabetes [ 11 ] and Alzheimer's disease [ 12 ]. Curcumin is a naturally occurring polyphenolic compound extracted from turmeric and has various pharmacological activities, including antioxidant, anti-inflammatory, immunomodulatory, hypolipidemic, glycemic control, and improving hepatic function as well as serum cortisol levels [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Turmeric, a powder of the rhizomes of Curcuma longa L. (Zingiberaceae), is a well-known spice additive that is ubiquitous in Asian cuisine [ 10 ]. Turmeric is also a staple component of Ayurveda and traditional Chinese medicine and has been used as a remedy for various chronic diseases, such as cardiovascular disease and diabetes [ 11 ] and Alzheimer's disease [ 12 ]. Curcumin is a naturally occurring polyphenolic compound extracted from turmeric and has various pharmacological activities, including antioxidant, anti-inflammatory, immunomodulatory, hypolipidemic, glycemic control, and improving hepatic function as well as serum cortisol levels [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports indicated that LPS-stimulated NO production in RAW 264 cells was inhibited by the constituents of Curcumae Longae Rhizoma and Saussureae Radix (20,21). Over the decades, several studies have been conducted on the anti-inflammatory effects of C. longa (22). In RAW 264 cells, curcumin, curcumol, and turmeronol, which are major components of Curcumae Longae Rhizoma, inhibited LPSinduced NO production by suppressing iNOS mRNA expression (20,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Turmeric is known to consist of numerous curcuminoids, which are bioactive phenolic compounds. Out of the over 100 individual curcuminoids known by now, curcumin is the major component in turmeric and accounts for approximately 77% of the whole extract [ 23 ]. Therefore, it is not surprising that treatment of microglial cells with curcumin showed a strong reduction of NO-release starting at concentrations of 5 µM, equaling 3,7 µg/mL at the highest concentration of 10 µM, while 500 µg/mL of the used TE contained 145 µg/mL curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…Turmeric consists of a variety of active metabolites, including curcumin, tetrahydrocurcumin (THC), and curcumenol, amongst others. Even though many studies have shown that these derivates exert a wide range of anti-inflammatory, anti-proliferative, and anti-oxidative properties [ 22 ], their individual contribution to the observed effects is still unclear [ 23 ]. For instance, treatment of cadmium-induced neuroinflammation with an essential oil from turmeric rhizomes prevented the increase of pro-inflammatory cytokines such as IL-6 or TNFα and prevented a decrease of IL-10 as anti-inflammatory mediator [ 24 ].…”
Section: Introductionmentioning
confidence: 99%